2021
DOI: 10.1002/chem.202103065
|View full text |Cite
|
Sign up to set email alerts
|

Insertion Chemistry of Lutetacyclopropene toward Unsaturated C−O/C−N Bonds

Abstract: Although the reaction chemistry of transition metallacyclopropenes has been well-established in the last decades, the reactivity of rare-earth metallacyclopropenes remains elusive. Herein, we report the reaction of lutetacyclopropene 1 toward a series of unsaturated molecules. The reaction of 1 with one equiv. of PhCOMe, Ar 1 CHO (Ar 1 = 2,6-Me 2 C 6 H 3 ), W(CO) 6 , and PhCH=NPh provided oxalutetacyclopentenes, metallacyclic lutetoxycarbene, and azalutetacyclopentene via 1,2-insertion of C=O, C�O, or C=N bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Until 2019, our group prepared the first series of rare-earth metallacyclopropenes from the chloride precursors of rare-earth metals, potassium graphite (KC 8 ), and alkynes . Further reactivity investigation revealed that the lutetacyclopropene and dysprosacyclopropene could couple with 1 or 2 equiv of alkyl and aryl nitriles to afford azametallacyclopentadienes A′ and η 2 -pyrimidine metallacycles C , respectively (Scheme b) . These results stimulated us to examine the reaction of rare-earth metallacyclopropenes with other types of nitriles.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Until 2019, our group prepared the first series of rare-earth metallacyclopropenes from the chloride precursors of rare-earth metals, potassium graphite (KC 8 ), and alkynes . Further reactivity investigation revealed that the lutetacyclopropene and dysprosacyclopropene could couple with 1 or 2 equiv of alkyl and aryl nitriles to afford azametallacyclopentadienes A′ and η 2 -pyrimidine metallacycles C , respectively (Scheme b) . These results stimulated us to examine the reaction of rare-earth metallacyclopropenes with other types of nitriles.…”
Section: Introductionmentioning
confidence: 52%
“…The Lu1–C3 distance (2.4131 Å) is in line with the Lu–C sp2 σ bond lengths. The Lu–N1 distance (2.2152(15) Å) is a little shorter than the Lu–N σ bond distance in reported azalutetacycles but comparable with the documented Lu–NH distances . In addition, the N1–C1 (1.370(2) Å) and C1–C4 (1.372(2) Å) distances in 4b correspond to the N–C (1.371(7) Å) and C–C (1.381(8) Å) bond lengths in 2a .…”
Section: Results and Discussionmentioning
confidence: 99%
“…New lanthanide metallacycles like azalutetacyclopentadienes, η 2 ‐pyrimidine dysprosium and a fused [5,6]lutetacycle as the first examples in rare‐earth organometallic chemistry were obtained [21b] . The insertion chemistry of lutetacyclopropene towards unsaturated CO and CN bonds was very recently published [21c] . Again, these papers show some similarities for the typical alkyne substitution of group 4 metallocene bis(trimethylsilyl)acetylene complexes with similar and other actinide alkyne complexes.…”
Section: Actinide Metallocene Bis(trimethylsilyl)acetylene Complexesmentioning
confidence: 92%
“…In the last few decades, investigations on the synthesis and reactivity of rare-earth-metal alkylidene complexes have been documented widely. 9–15 Our previous studies on amidinate rare-earth-metal carbene derivatives have also shown the unique reactivity of μ 3 -CH 2 dianions. 16,17 The results indicate that there are significant ligand effects on the structure and reactivity of these complexes.…”
Section: Introductionmentioning
confidence: 95%